2020
DOI: 10.3390/microorganisms8111740
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Characterization and Phylogenetic Distribution of Extracellular Matrix Components in the Model Rhizobacteria Pseudomonas fluorescens F113 and Other Pseudomonads

Abstract: Biofilms are complex structures that are crucial during host–bacteria interaction and colonization. Bacteria within biofilms are surrounded by an extracellular matrix (ECM) typically composed of proteins, polysaccharides, lipids, and DNA. Pseudomonads contain a variety of ECM components, some of which have been extensively characterized. However, neither the ECM composition of plant-associated pseudomonads nor their phylogenetic distribution within the genus has been so thoroughly studied. In this work, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 130 publications
0
49
1
Order By: Relevance
“…Among all the exopolysaccharides that are produced by plant-associated Pseudomonas [ 72 ], those that have been mainly studied are alginate, cellulose, and Psl ( Table 1 ). A description of their functions in biofilm formation and architecture and their ecological significance during pathogenic and beneficial plant–bacteria interactions are listed below.…”
Section: Main Exopolysaccharides Produced By Plant-associated mentioning
confidence: 99%
See 4 more Smart Citations
“…Among all the exopolysaccharides that are produced by plant-associated Pseudomonas [ 72 ], those that have been mainly studied are alginate, cellulose, and Psl ( Table 1 ). A description of their functions in biofilm formation and architecture and their ecological significance during pathogenic and beneficial plant–bacteria interactions are listed below.…”
Section: Main Exopolysaccharides Produced By Plant-associated mentioning
confidence: 99%
“…Several biosynthesis and regulation mechanisms have been described for bacterial cellulose, but a common role of this component is to facilitate the establishment of efficient host-bacteria interactions [ 95 ]. Previous studies reported that several plant-associated Pseudomonas species can produce cellulose, including the plant-associated pathogenic bacteria P. syringae , P. asplenii , P. marginalis , P. corrugate, and P. savastanoi and beneficial bacteria, such as P. fluorescens and P. putida [ 72 , 93 , 94 ]. Within the Pseudomonas genus, P. fluorescens SBW25 (SBW25) is traditionally used as the model strain for the study of bacterial cellulose.…”
Section: Main Exopolysaccharides Produced By Plant-associated mentioning
confidence: 99%
See 3 more Smart Citations